The Effectiveness of the Practice-Based Predict Observe Explain (POE) Model on Students' Critical Thinking Skills and Learning Motivation - Jumarsa Jumarsa; Nurlena Andalia; Jalaluddin Jalaluddin; Musriadi Musriadi; Muslem Daud (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
Laboratory activities in the Entomology course at the Biology Education Study Program, Universitas Serambi Mekkah, have not fully optimized students’ active engagement, resulting in limited development of critical thinking skills and learning motivation. Practical activities have tended to focus on procedural completion and have not been systematically integrated with scientific thinking processes. This study aimed to examine the effectiveness of a practicum-based Predict Observe Explain (POE) learning model on students’ critical thinking skills and learning motivation. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The sample consisted of 38 Biology Education students enrolled in the Entomology course in the 2025/2026 academic year. Data were collected through observations, critical thinking tests, learning motivation questionnaires, and interviews, and analyzed using paired sample t-tests, N-Gain, and percentage analysis. The results showed that the practicum-based POE model was implemented very well (94.02%). A significant improvement in critical thinking skills was found, with an average N-Gain of 0.51 (moderate category), while learning motivation was classified as very high (87%). Therefore, the practicum-based POE model is effective in improving students’ critical thinking skills and learning motivation in the Entomology course.